Wirtualny komponent informacyjno-edukacyjnego środowiska szkoły wyższej jako warunek przygotowania nauczyciela = Virtual component of information and educational environment for higher education as a condition of teacher preparation - Tumaleva, Elena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The objectives and tasks of information-educational environment for higher education are presented. These include: monitoring and information support of teaching processes, scientific research; career counselling for students. The implementation of tasks for information and education environment at the examples of the universities of the Russian Federation is presented. The training rules for specialists in the field of information technology as well as the responsibility for creating their own information environment are described at the example of Herzen National State University. The factors of the effectiveness of information environment are analyzed. Keywords: information and educational environment, information technology, the virtual component of higher education, multi-level teacher training
Keywords: środowisko informacyjno-edukacyjne; technologie IT; wirtualny komponent szkoły wyższej; wielopoziomowość kształcenia pedagogicznego; information and educational environment; information technology; virtual component of higher education; multi-level teacher training